Pengaruh Corporate Governance terhadap Peringkat Sukuk Perusahaan di Indonesia - Mufida Prafitri; Y. Anni Aryani (Jurnal Ilmiah Ekonomi Islam, 2019)
This study aims to examine the effect of corporate governance on corporate sukuk ratings in Indonesia. The proxies of corporate governance are institutional ownership, managerial ownership, board independence commissioner. audit committees, and audit quality. The control variables taken in this study include board size and leverage. This study took a population of sukuk publishing companies which is published during the period 2007-2016 and ranked by PEFINDO. Using the purposive sampling method, the number of sample obtained 18 companies. This study uses a datapanel model with software Eviews 10 for method analysis. The results prove that institusional ownership and managerial ownership, both of them affect on corporate sukuk ratings. Board independence commissioner, audit committees, and audit quality don’t have an effect on Corporate sukuk ratings. The control variables are board size and leverage have an effect on corporate sukuk ratings. Keyword: Sukuk, Corporate Governance, Corporate Sukuk Rating